2004
DOI: 10.1530/rep.1.00015
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin requirements for dominant follicle selection in GnRH agonist-treated cows

Abstract: A study was conducted to examine the effects of gonadotropins on ovarian follicular development and differentiation in GnRH agonist (GnRHa)-treated cattle. Holstein cows were allotted into two pre-treatment groups: controls (n 5 5) and GnRHa-treated (n 5 9). Ovaries were removed from control cows on day 5 following a synchronized estrus. Treatment with GnRHa resulted in follicular arrest at < 5 mm. Following follicular arrest, GnRHa-treated cows received a constant infusion of FSH for 96 h (GnRHa/FSH), with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
4
10
0
1
Order By: Relevance
“…Indeed, ovarian weight, follicular activity, and number of corpora lutea did not differ between animals receiving Fca alone and those receiving either the dually active chimera or the FcaCCGba combination. These observations are consistent with previous reports noting significant FSH-induced follicle development without coincident estrogen production in LH-deficient sheep (Picton et al 1990, Campbell et al 1998, cattle (Hampton et al 2004), and primates (Karnitis et al 1994, Zelinski-Wooten et al 1995.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, ovarian weight, follicular activity, and number of corpora lutea did not differ between animals receiving Fca alone and those receiving either the dually active chimera or the FcaCCGba combination. These observations are consistent with previous reports noting significant FSH-induced follicle development without coincident estrogen production in LH-deficient sheep (Picton et al 1990, Campbell et al 1998, cattle (Hampton et al 2004), and primates (Karnitis et al 1994, Zelinski-Wooten et al 1995.…”
Section: Discussionsupporting
confidence: 93%
“…Our results concerning theca cells are consistent with those of a previous study that also tested the role of LH pulses in follicle growth [60]. Those researchers treated cows with a GnRH agonist until follicle growth greater than 5 mm in diameter was inhibited.…”
Section: Discussionsupporting
confidence: 91%
“…Suppression of LH secretion by P 4 treatment at the time of follicular deviation decreases follicular E 2 and free IGF1 concentrations and increases IGF-binding protein 2 (IGFBP2) concentration in the follicular fluid of the dominant follicle (Ginther et al 2001b). Pulsatile LH infusion into GNRH agonist-treated cows and during the follicular wave of cyclic cows demonstrated that the LH is required for mRNA expression of steroidogenic enzymes in both granulosa and theca cells, which is responsible for a dramatic increase in the follicular fluid concentration of E 2 and further follicular growth (Crowe et al 2001, Manikkam et al 2001, Hampton et al 2004. We postulated that enhanced LH pulses in the CL-absent cows permit accelerated F2 growth and thus stimulate E 2 production.…”
Section: Discussionmentioning
confidence: 99%